2011
DOI: 10.1111/j.1471-6712.2011.00918.x
|View full text |Cite
|
Sign up to set email alerts
|

Abuse in health care: a concept analysis

Abstract: Aims and objectives. To analyze the concept of abuse in health care. This analysis also covers how abuse in health care is different from the related concepts of medical error, patient satisfaction, and personal identity threat.Background. Abuse in health care is an emerging concept in need of a clear analysis and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 33 publications
1
44
0
5
Order By: Relevance
“…It has been well-documented that female and male patients can experience suffering from encounters in health care, which is not related to their disease and even despite a medically correct treatment (Brüggemann et al, 2012a;Coyle, 1999;Levinson and Shojania, 2011;Swahnberg et al, 2009a;Swahnberg et al, 2007a;Söderberg et al, 2011). These incidents do not only imply immediate and long-term suffering, but they can also affect a patient's confidence in the health care system (Swahnberg et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well-documented that female and male patients can experience suffering from encounters in health care, which is not related to their disease and even despite a medically correct treatment (Brüggemann et al, 2012a;Coyle, 1999;Levinson and Shojania, 2011;Swahnberg et al, 2009a;Swahnberg et al, 2007a;Söderberg et al, 2011). These incidents do not only imply immediate and long-term suffering, but they can also affect a patient's confidence in the health care system (Swahnberg et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…A study among long-term sick-listed patients showed that health care encounters devoid of respect can impair their ability to return to work (Lynöe et al, 2011), pointing at far reaching consequences of untoward health care encounters. Harmful encounters or those devoid of care, as seen from patients' perspectives, have been labeled abuse in health care (Brüggemann et al, 2012a). …”
Section: Introductionmentioning
confidence: 99%
“…In qualitative interview studies, female patients described AHC as the feeling of "being nullified" (10), and male patients as "being mentally pinioned" (11). Currently it is not known why AHC takes place and can prevail (7).…”
Section: Abuse In Health Carementioning
confidence: 99%
“…One major critique is that patients' untoward experiences in health care are not adequately captured by patient satisfaction studies (5). A recent concept analysis showed that events of abuse in health care (AHC) are easily missed out in patient satisfaction studies (7). As these events are characterized by patients losing their value as human beings and as uncaring, regardless of staff's intentions (3), this should be seen as a major ethical problem for the health care system.…”
Section: Introductionmentioning
confidence: 99%
“…[9] The phenomenon "AHC" has been described in several studies [10][11][12][13] and has been defined as "patients' subjective experiences of encounters with the health care system, characterized by devoid of care, where patients suffer and feel they lose their value as human beings" [p. 123]. [14] AHC occurs in a variety of healthcare settings. [8,10,11,[15][16][17] Experiences of AHC among female patients in gynecological settings in five Nordic countries were investigated and a prevalence of 13%-28% was reported in all healthcare contexts.…”
Section: Introductionmentioning
confidence: 99%